496Higher predicted 10-year risk for cardiovascular disease in primary care consulters for osteoarthritis. (2nd September 2021) - Huang, Miss Xiaoyang; Yu, Dahai; Wilkie, Ross; Mamas, Mamas
Abstract: Background: Osteoarthritis (OA) has a major impact on the global burden of disease and is associated with poorer cardiovascular disease (CVD) outcomes. However it's unclear whether people with OA have higher long-term (10-year) CVD risk compared to people without OA. This study uses electronic health record (EHR) data from a national representative database to calculate the Framingham-score (a gender-specific risk algorithm) to test the hypothesis that OA consulters have higher long-term CVD risk than non-OA consulters. Methods: 205, 368 incident OA consulters with 1:1 age, gender, and practice-matched non-OA controls extracted from Clinical Practice Research Datalink (CPRD) were included. All predictors extracted from EHRs within three years prior to the index consultation were used to fit the Framingham-score. Absolute difference (AR) and relative rate ratio (RR) in the proportion of high-risk (predicted-risk ≥20%) individuals between OA and controls were estimated using Poisson regression. Results: The proportion of high-risk individuals was higher in consulters for OA (5.69 (95% confidence interval (CI): 5.59-5.79)%) cf. 4.37 (4.28-4.46)%). The adjusted AR and RR was (1.94 (95%CI: 1.78-2.10) %) and (1.30 (1.27-1.34)), respectively. Conclusions: This study confirms the expected higher predicted 10-year CVD risk in OA consulters compared to controls. This suggests that OA consulters could be a target group for more proactive interventions to prevent CVD events. Key messages: OA consulters have a higher CVD risk predicted by Framingham-score calculated using EHRs than controls; OA consulters are a high risk group that can be considered as a target group for proactive prevention interventions for CVD.